2022
DOI: 10.3390/cancers14153653
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Cutaneous Squamous Cell Carcinoma Management

Abstract: cSCC is increasing in prevalence due to increased lifespans and improvements in survival for conditions that increase the risk of cSCC. The absolute mortality of cSCC exceeds melanoma in the United States and approaches that of melanoma worldwide. This review presents significant changes in the management of cSCC, focusing on improvements in risk stratification, new treatment options, optimization of existing treatments, and prevention strategies. One major breakthrough in cSCC treatment is the advent of immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 130 publications
(188 reference statements)
0
15
0
Order By: Relevance
“…The first immunotherapy drug used for the treatment of CSCC was intralesional interferon [ 48 ]. Over the past 3 decades, there has been increased knowledge regarding the immune system’s key role in CSCC pathogenesis [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…The first immunotherapy drug used for the treatment of CSCC was intralesional interferon [ 48 ]. Over the past 3 decades, there has been increased knowledge regarding the immune system’s key role in CSCC pathogenesis [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Farberg et al have suggested intensifying management in high-risk groups and incorporating 40-GEP within NCCN guideline recommendations [16]. Despite the reported incremental improvements in the prognostic and clinical usefulness of 40-GEP, it has not yet been integrated into the guidelines of the NCCN nor the American Academy of Dermatology [4, 24,25].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…The cancer types that are approved for treatment with ICIs continue to increase every year, and at present, 22 types of cancer are included in the approval list [26,29,36]. The introduction of ICIs has ushered a new age in treating advanced and metastatic malignancies, as they are better tolerated and often more effective compared with chemotherapy and radiotherapy [10 ▪ ].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Surgical resection alone is seldom sufficient in cancer treatment. A more recent option for the treatment of cancer is immunotherapy, particularly with immune checkpoint inhibitors (ICIs), which have been shown to be well tolerated compared with chemotherapy or radiotherapy [10 ▪ ]. However, the use of immunotherapy in SOTRs, in whom immunosuppression is the key strategy for preventing allograft rejection, is considered risky, as it could broadly unleash the immune system response, including against the transplanted organ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation